Aqueous Synthesis of Sub-11 nm Fe-Cu Oxides and Alloy Nanostructures: Structural and Morphological studies - Raquel Zuñiga-Lechuga; Alfredo Vilchis-Nestor; Raúl Morales-Luckie; Victor Sanchez-Mendieta (Nanochemistry Research)
Fe and Cu oxides and Fe-Cu alloy nanostructures (FeCuNS) were obtained using a facile chemical reduction of different mass ratios of FeCl2∙4H2O and CuCl2∙2H2O with NaBH4 in an aqueous solution, under nitrogen atmosphere. FeCuNS were prepared in three different Fe:Cu ratios: 75:25, 50:50, and 25:75 wt. %, by an aqueous reduction. FeCuNS were characterized by Scanning Electron Microscopy (SEM), X-Ray Photoelectron Spectroscopy (XPS), X-Ray Diffraction (XRD), Transmission Electron Microscopy (TEM), and High-Resolution TEM (HRTEM), and their textural properties were determined using nitrogen physisorption. Synthesized FeCuNS sizes ranged from 2.2 to 11 nm, having an irregular quasi-spherical morphology. The main phases in these nanostructures, as determined by XRD, are Fe2O3, Fe3O4 and CuFe2O4; the main peak obtained at 2θ = 43.33° confirmed the formation of the nanoalloy Fe-Cu, as FeCu4 (JCPDS No.065-7002) in the 50:50 and 25:75 wt.% FeCuNS samples, which can be indexed as a face-centered cubic structure (FCC). An XPS study performed on these nanostructures allowed for confirming the formation of the FeCu4 alloy, alongside other metallic oxide main phases.